Clinical aspects of the use of ribociclib - A. A. Markovich; M. V. Kalugin; O. О. Gordeeva; M. Zh. Yakoobova (Медицинский совет, 2020)
Luminal metastatic HER2-negative breast cancer remains one of the most common cancers in oncological practice. This disease still remains incurable. Endocrine therapy remained the standard therapy of choice for disseminated patients for a long time. The search for new effective drugs, development of strategies that can overcome primary and secondary resistance to endocrinotherapy has shown that the CDK4/6-inhibitors group can improve not only the short-term treatment outcomes, but also affect the overall survival of patients, which has been demonstrated in a number of phase III studies. Along with that, the use of CDK4/6 inhibitors maintains a good quality of life, allows patients to maintain professional and social activities, which is of great importance for long-term prospects. Given that the endocrine therapy combined with CDK4/6-inhibitors today is the new standard of therapy in patients with luminal HER2- negative breast cancer, knowing how to use this therapy in daily clinical practice is crucial. Know and apply innovative drugs in clinical practice and the management of regimen toxicity always my work demands close application. This article provides an overview of the data on the efficacy of ribociclib based on phase III registration studies. It also presents its own clinical experience demonstrating the feasibility of using a new group of drugs in patients both in pre- and postmenopausal women. The authors discussed the issues related to the modification of the regimen due to the toxicity of therapy, in particular, neutropenia and hepatotoxicity. They also showed the possibility of managing adverse events with the preservation of a long-term effect with no loss in quality of life.